Tinjauan Undang-Undang Nomor 2 Tahun 2014 Terhadap Praktik Penerapan Honorarium Notaris - Abdul Manan; Abu Tamrin; Muhamad Nuzul Wibawa (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2019)
Abstract The practice of applying a Notary honorarium that is not in accordance with Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Position, that a Notary has set a tariff below the standard. This study uses empirical normative methods, literature studies and case approaches. The results of the sutdy show that the practice of applying Notary honorariums tha are not in accordance with Law Number 2 of 2014 concerning Amendments to Law Number 2004 concerning Notary Position, in practice that Notaries have violated the provisions of Article 13 Paragraph (3), Article 4 Paragraph (9), and Article 4 Paragraph (10) Notary Code of Ethics, and sanctions that can be imposed on Notaries who do not apply honorarium according to Law Number 2 Year 2014 concerning Amendments to Law Number 30 Year 2004 concerning Notary Position stipulated in Article 6 Notary Code of Ethics.Keywords: Notary, Honorarium, Notary Supervisory Board